lean2/library/theories/analysis/bounded_linear_operator.lean

590 lines
23 KiB
Text
Raw Normal View History

/-
Copyright (c) 2016 Robert Y. Lewis. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Author: Robert Y. Lewis
Bounded linear operators
-/
import .normed_space .real_limit algebra.module algebra.homomorphism
open real nat classical topology set
--open normed_vector_space (this confuses lots of stuff??)
noncomputable theory
namespace analysis
-- define bounded linear operators and basic instances
section bdd_lin_op
structure is_bdd_linear_map [class] {V W : Type} [normed_vector_space V] [normed_vector_space W] (f : V → W)
extends is_module_hom f :=
(op_norm : ) (op_norm_pos : op_norm > 0) (op_norm_bound : ∀ v : V, ∥f v∥ ≤ op_norm * ∥v∥)
theorem is_bdd_linear_map_id [instance] (V : Type) [normed_vector_space V] : is_bdd_linear_map (λ x : V, x) :=
begin
fapply is_bdd_linear_map.mk,
repeat (intros; reflexivity),
exact 1,
exact zero_lt_one,
intro, rewrite one_mul, apply le.refl
end
theorem is_bdd_linear_map_zero [instance] (V W : Type) [normed_vector_space V] [normed_vector_space W] :
is_bdd_linear_map (λ x : V, (0 : W)) :=
begin
fapply is_bdd_linear_map.mk,
all_goals intros,
rewrite zero_add,
rewrite smul_zero,
exact 1,
exact zero_lt_one,
rewrite [norm_zero, one_mul],
apply norm_nonneg
end
theorem is_bdd_linear_map_add [instance] {V W : Type} [normed_vector_space V] [normed_vector_space W]
(f g : V → W) [Hbf : is_bdd_linear_map f] [Hbg : is_bdd_linear_map g] :
is_bdd_linear_map (λ x, f x + g x) :=
begin
fapply is_bdd_linear_map.mk,
all_goals intros,
{rewrite [hom_add f, hom_add g],-- (this takes 4 seconds: rewrite [2 hom_add])
simp},
{rewrite [hom_smul f, hom_smul g, smul_left_distrib]},
{exact is_bdd_linear_map.op_norm _ _ f + is_bdd_linear_map.op_norm _ _ g},
{apply add_pos,
repeat apply is_bdd_linear_map.op_norm_pos},
{apply le.trans,
apply norm_triangle,
rewrite right_distrib,
apply add_le_add,
repeat apply is_bdd_linear_map.op_norm_bound}
end
theorem is_bdd_linear_map_smul [instance] {V W : Type} [normed_vector_space V] [normed_vector_space W]
(f : V → W) (c : ) [Hbf : is_bdd_linear_map f] : is_bdd_linear_map (λ x, c • f x) :=
begin
apply @decidable.cases_on (c = 0),
exact _,
{intro Hcz,
rewrite Hcz,
have Hfe : (λ x : V, (0 : ) • f x) = (λ x : V, 0), from funext (λ x, !zero_smul),
rewrite Hfe,
apply is_bdd_linear_map_zero},
intro Hcnz,
fapply is_bdd_linear_map.mk,
all_goals intros,
{rewrite [hom_add f, smul_left_distrib]},
{rewrite [hom_smul f, -*mul_smul, {c*r}mul.comm]},
{exact (abs c) * is_bdd_linear_map.op_norm _ _ f},
{have Hpos : abs c > 0, from abs_pos_of_ne_zero Hcnz,
apply mul_pos,
assumption,
apply is_bdd_linear_map.op_norm_pos},
{rewrite [norm_smul, mul.assoc],
apply mul_le_mul_of_nonneg_left,
apply is_bdd_linear_map.op_norm_bound,
apply abs_nonneg}
end
theorem is_bdd_linear_map_neg [instance] {V W : Type} [normed_vector_space V] [normed_vector_space W]
(f : V → W) [Hbf : is_bdd_linear_map f] : is_bdd_linear_map (λ x, -f x) :=
begin
have H : (λ x : V, -f x) = (λ x : V, (-1 : ) • f x), from funext (λ x, eq.symm !neg_one_smul),
rewrite H,
apply is_bdd_linear_map_smul
end
-- this can't be an instance because things loop
theorem is_bdd_linear_map_comp {U V W : Type} [normed_vector_space U] [normed_vector_space V]
[normed_vector_space W] (f : V → W) (g : U → V) [is_bdd_linear_map f] [is_bdd_linear_map g] :
is_bdd_linear_map (λ u, f (g u)) :=
begin
fapply is_bdd_linear_map.mk,
all_goals intros,
{rewrite [hom_add g, hom_add f]},
{rewrite [hom_smul g, hom_smul f]},
{exact is_bdd_linear_map.op_norm _ _ f * is_bdd_linear_map.op_norm _ _ g},
{apply mul_pos, repeat apply is_bdd_linear_map.op_norm_pos},
{apply le.trans,
apply is_bdd_linear_map.op_norm_bound _ _ f,
apply le.trans,
apply mul_le_mul_of_nonneg_left,
apply is_bdd_linear_map.op_norm_bound _ _ g,
apply le_of_lt !is_bdd_linear_map.op_norm_pos,
rewrite *mul.assoc,
apply le.refl}
end
variables {V W : Type}
variables [HV : normed_vector_space V] [HW : normed_vector_space W]
include HV HW
variable f : V → W
variable [Hf : is_bdd_linear_map f]
include Hf
definition op_norm := is_bdd_linear_map.op_norm _ _ f
theorem op_norm_pos : op_norm f > 0 := is_bdd_linear_map.op_norm_pos _ _ f
theorem op_norm_bound (v : V) : ∥f v∥ ≤ (op_norm f) * ∥v∥ := is_bdd_linear_map.op_norm_bound _ _ f v
theorem bdd_linear_map_continuous : continuous f :=
begin
apply continuous_of_forall_continuous_at,
intro x,
apply normed_vector_space.continuous_at_intro,
intro ε Hε,
existsi ε / (op_norm f),
split,
apply div_pos_of_pos_of_pos Hε !op_norm_pos,
intro x' Hx',
rewrite [-hom_sub f],
apply lt_of_le_of_lt,
apply op_norm_bound f,
rewrite [-@mul_div_cancel' _ _ ε (op_norm f) (ne_of_gt !op_norm_pos)],
apply mul_lt_mul_of_pos_left,
exact Hx',
apply op_norm_pos
end
end bdd_lin_op
-- define Frechet derivative and basic properties
section frechet_deriv
variables {V W : Type}
variables [HV : normed_vector_space V] [HW : normed_vector_space W]
include HV HW
definition has_frechet_deriv_at (f A : V → W) [is_bdd_linear_map A] (x : V) :=
(λ h : V, ∥f (x + h) - f x - A h ∥ / ∥ h ∥) ⟶ 0 [at 0]
lemma diff_quot_cts {f A : V → W} [HA : is_bdd_linear_map A] {y : V} (Hf : has_frechet_deriv_at f A y) :
continuous_at (λ h, ∥f (y + h) - f y - A h∥ / ∥h∥) 0 :=
begin
apply normed_vector_space.continuous_at_intro,
intro ε Hε,
cases normed_vector_space.approaches_at_dest Hf Hε with δ Hδ,
existsi δ,
split,
exact and.left Hδ,
intro x' Hx',
cases em (x' = 0) with Heq Hneq,
{rewrite [Heq, norm_zero, div_zero, sub_zero, norm_zero], apply Hε},
{rewrite [norm_zero, div_zero],
apply and.right Hδ,
repeat assumption}
end
theorem is_bdd_linear_map_of_eq {A B : V → W} [HA : is_bdd_linear_map A] (HAB : A = B) :
is_bdd_linear_map B :=
begin
fapply is_bdd_linear_map.mk,
all_goals try rewrite -HAB,
{apply hom_add},
{apply hom_smul},
{exact op_norm A},
{exact op_norm_pos A},
{rewrite -HAB, apply op_norm_bound}
end
definition is_frechet_deriv_at_of_eq {f A : V → W} [is_bdd_linear_map A] {x : V}
(Hfd : has_frechet_deriv_at f A x) {B : V → W} (HAB : A = B) :
@has_frechet_deriv_at _ _ _ _ f B (is_bdd_linear_map_of_eq HAB) x :=
begin
unfold has_frechet_deriv_at,
rewrite -HAB,
apply Hfd
end
theorem has_frechet_deriv_at_intro {f A : V → W} [is_bdd_linear_map A] {x : V}
(H : ∀ ⦃ε : ℝ⦄, ε > 0 →
(∃ δ : , δ > 0 ∧ ∀ ⦃x' : V⦄, x' ≠ 0 ∧ ∥x'∥ < δ → ∥f (x + x') - f x - A x'∥ / ∥x'∥ < ε)) :
has_frechet_deriv_at f A x :=
begin
apply normed_vector_space.approaches_at_intro,
intros ε Hε,
cases H Hε with δ Hδ,
cases Hδ with Hδ Hδ',
existsi δ,
split,
assumption,
intros x' Hx'1 Hx'2,
show abs (∥f (x + x') - f x - A x'∥ / ∥x'∥ - 0) < ε, begin
have H : ∥f (x + x') - f x - A x'∥ / ∥x'∥ ≥ 0,
from div_nonneg_of_nonneg_of_nonneg !norm_nonneg !norm_nonneg,
rewrite [sub_zero, abs_of_nonneg H],
apply Hδ',
split,
assumption,
rewrite [-sub_zero x'],
apply Hx'1
end
end
theorem has_frechet_deriv_at_elim {f A : V → W} [is_bdd_linear_map A] {x : V} (H : has_frechet_deriv_at f A x) :
∀ ⦃ε : ℝ⦄, ε > 0 →
(∃ δ : , δ > 0 ∧ ∀ ⦃x' : V⦄, x' ≠ 0 ∧ ∥x'∥ < δ → ∥f (x + x') - f x - A x'∥ / ∥x'∥ < ε) :=
begin
intros ε Hε,
cases normed_vector_space.approaches_at_dest H Hε with δ Hδ,
cases Hδ with Hδ Hδ',
existsi δ,
split,
assumption,
intros x' Hx',
rewrite [-sub_zero x' at Hx' {2}],
have Hδ'' : abs (∥f (x + x') - f x - A x'∥ / ∥x'∥ - 0) < ε, from Hδ' (and.right Hx') (and.left Hx'),
have Hpos : ∥f (x + x') - f x - A x'∥ / ∥x'∥ ≥ 0, from div_nonneg_of_nonneg_of_nonneg !norm_nonneg !norm_nonneg,
rewrite [sub_zero at Hδ'', abs_of_nonneg Hpos at Hδ''],
assumption
end
structure frechet_diffable_at [class] (f : V → W) (x : V) :=
(A : V → W) [HA : is_bdd_linear_map A] (is_fr_der : has_frechet_deriv_at f A x)
variables f g : V → W
variable x : V
definition frechet_deriv_at [Hf : frechet_diffable_at f x] : V → W :=
frechet_diffable_at.A _ _ f x
definition frechet_deriv_at_is_bdd_linear_map [instance] (f : V → W) (x : V) [Hf : frechet_diffable_at f x] :
is_bdd_linear_map (frechet_deriv_at f x) :=
frechet_diffable_at.HA _ _ f x
theorem frechet_deriv_spec [Hf : frechet_diffable_at f x] :
(λ h : V, ∥f (x + h) - f x - (frechet_deriv_at f x h) ∥ / ∥ h ∥) ⟶ 0 [at 0] :=
frechet_diffable_at.is_fr_der _ _ f x
theorem has_frechet_deriv_at_const (w : W) : has_frechet_deriv_at (λ v : V, w) (λ v : V, 0) x :=
begin
apply normed_vector_space.approaches_at_intro,
intros ε Hε,
existsi 1,
split,
exact zero_lt_one,
intros x' Hx' _,
rewrite [2 sub_self, norm_zero],
krewrite [zero_div, sub_zero, norm_zero],
assumption
end
theorem has_frechet_deriv_at_id : has_frechet_deriv_at (λ v : V, v) (λ v : V, v) x :=
begin
apply normed_vector_space.approaches_at_intro,
intros ε Hε,
existsi 1,
split,
exact zero_lt_one,
intros x' Hx' _,
have x + x' - x - x' = 0, by simp,
rewrite [this, norm_zero, zero_div, sub_self, norm_zero],
exact Hε
end
theorem has_frechet_deriv_at_smul (c : ) {A : V → W} [is_bdd_linear_map A]
(Hf : has_frechet_deriv_at f A x) : has_frechet_deriv_at (λ y, c • f y) (λ y, c • A y) x :=
begin
eapply @decidable.cases_on (abs c = 0),
exact _,
{intro Hc,
have Hz : c = 0, from eq_zero_of_abs_eq_zero Hc,
have Hfz : (λ y : V, (0 : ) • f y) = (λ y : V, 0), from funext (λ y, !zero_smul),
--have Hfz' : (λ x : V, (0 : ) • A x) = (λ x : V, 0), from funext (λ y, !zero_smul),
-- rewriting Hfz' produces type-incorrect term
rewrite [Hz, Hfz],
apply metric_space.approaches_at_intro,
intro ε Hε,
existsi 1,
split,
exact zero_lt_one,
intro x' Hx' _,
rewrite [zero_smul, *sub_zero, norm_zero],
krewrite [zero_div, dist_self],
exact Hε},
intro Hcnz,
apply normed_vector_space.approaches_at_intro,
intros ε Hε,
have Hεc : ε / abs c > 0, from div_pos_of_pos_of_pos Hε (lt_of_le_of_ne !abs_nonneg (ne.symm Hcnz)),
cases normed_vector_space.approaches_at_dest Hf Hεc with δ Hδ,
cases Hδ with Hδp Hδ,
existsi δ,
split,
assumption,
intro x' Hx' _,
show abs ((∥c • f (x + x') - c • f x - c • A x'∥ / ∥x'∥ - 0)) < ε, begin
rewrite [sub_zero, -2 smul_sub_left_distrib, norm_smul],
krewrite mul_div_assoc,
rewrite [abs_mul, abs_abs, -{ε}mul_div_cancel' Hcnz],
apply mul_lt_mul_of_pos_left,
have Hδ' : abs (∥f (x + x') - f x - A x'∥ / ∥x'∥ - 0) < ε / abs c, from Hδ Hx' a,
rewrite sub_zero at Hδ',
apply Hδ',
apply lt_of_le_of_ne,
apply abs_nonneg,
apply ne.symm,
apply Hcnz
end
end
theorem has_frechet_deriv_at_neg {A : V → W} [is_bdd_linear_map A]
(Hf : has_frechet_deriv_at f A x) : has_frechet_deriv_at (λ y, - f y) (λ y, - A y) x :=
begin
apply has_frechet_deriv_at_intro,
intros ε Hε,
cases has_frechet_deriv_at_elim Hf Hε with δ Hδ,
existsi δ,
split,
exact and.left Hδ,
intro x' Hx',
rewrite [-norm_neg, neg_sub, sub_neg_eq_add, sub_add_eq_sub_sub, sub_neg_eq_add,
add_sub_assoc, add.comm, -sub_eq_add_neg],
apply and.right Hδ,
assumption
end
theorem has_frechet_deriv_at_add (A B : V → W) [is_bdd_linear_map A] [is_bdd_linear_map B]
(Hf : has_frechet_deriv_at f A x) (Hg : has_frechet_deriv_at g B x) :
has_frechet_deriv_at (λ y, f y + g y) (λ y, A y + B y) x :=
begin
have Hle : ∀ h, ∥f (x + h) + g (x + h) - (f x + g x) - (A h + B h)∥ / ∥h∥ ≤
∥f (x + h) - f x - A h∥ / ∥h∥ + ∥g (x + h) - g x - B h∥ / ∥h∥, begin
intro h,
cases em (∥h∥ > 0) with Hh Hh,
krewrite div_add_div_same,
apply div_le_div_of_le_of_pos,
have Hfeq : f (x + h) + g (x + h) - (f x + g x) - (A h + B h) =
(f (x + h) - f x - A h) + (g (x + h) - g x - B h), by simp,
rewrite Hfeq,
apply norm_triangle,
exact Hh,
have Hhe : ∥h∥ = 0, from eq_of_le_of_ge (le_of_not_gt Hh) !norm_nonneg,
krewrite [Hhe, *div_zero, zero_add],
eapply le.refl
end,
have Hlimge : (λ h, ∥f (x + h) - f x - A h∥ / ∥h∥ + ∥g (x + h) - g x - B h∥ / ∥h∥) ⟶ 0 [at 0], begin
rewrite [-zero_add 0],
apply add_approaches,
apply Hf,
apply Hg
end,
have Hlimle : (λ (h : V), (0 : )) ⟶ 0 [at 0], by apply approaches_constant,
apply approaches_squeeze Hlimle Hlimge,
apply filter.eventually_of_forall,
intro y,
apply div_nonneg_of_nonneg_of_nonneg,
repeat apply norm_nonneg,
apply filter.eventually_of_forall,
apply Hle
end
open topology
theorem continuous_at_of_diffable_at [Hf : frechet_diffable_at f x] : continuous_at f x :=
begin
apply normed_vector_space.continuous_at_intro,
intros ε Hε,
note Hfds := normed_vector_space.approaches_at_dest (frechet_deriv_spec f x) Hε,
cases Hfds with δ Hδ,
cases Hδ with Hδ Hδ',
existsi min δ ((ε / 2) / (ε + op_norm (frechet_deriv_at f x))),
split,
{apply lt_min,
exact Hδ,
repeat apply div_pos_of_pos_of_pos,
exact Hε,
apply two_pos,
apply add_pos Hε !op_norm_pos},
{intro x' Hx',
cases em (x' - x = 0) with Heq Hneq,
rewrite [eq_of_sub_eq_zero Heq, sub_self, norm_zero], assumption,
have Hx'x : x' - x ≠ 0 ∧ ∥(x' - x) - 0∥ < δ, from and.intro Hneq begin
rewrite sub_zero,
apply lt_of_lt_of_le,
apply Hx',
apply min_le_left
end,
have Hx'xp : ∥x' - x∥ > 0, from norm_pos_of_ne_zero Hneq,
have Hδ'' : abs (∥f (x + (x' - x)) - f x - frechet_deriv_at f x (x' - x)∥ / ∥x' - x∥ - 0) < ε,
from Hδ' (and.right Hx'x) (and.left Hx'x),
have Hnn : ∥f (x + (x' - x)) - f x - frechet_deriv_at f x (x' - x)∥ / ∥x' - x∥ ≥ 0,
from div_nonneg_of_nonneg_of_nonneg !norm_nonneg !norm_nonneg,
rewrite [sub_zero at Hδ'', abs_of_nonneg Hnn at Hδ'', add.comm at Hδ'', sub_add_cancel at Hδ''],
note H1 := lt_mul_of_div_lt_of_pos Hx'xp Hδ'',
have H2 : f x' - f x = f x' - f x - frechet_deriv_at f x (x' - x) + frechet_deriv_at f x (x' - x),
by rewrite sub_add_cancel, --by simp, (simp takes .5 seconds to do this!)
rewrite H2,
apply lt_of_le_of_lt,
apply norm_triangle,
apply lt.trans,
apply add_lt_add_of_lt_of_le,
apply H1,
apply op_norm_bound (!frechet_deriv_at),
rewrite [-add_halves ε at {2}],
apply add_lt_add,
let on := op_norm (frechet_deriv_at f x),
exact calc
ε * ∥x' - x∥ < ε * min δ ((ε / 2) / (ε + on)) : mul_lt_mul_of_pos_left Hx' Hε
... ≤ ε * ((ε / 2) / (ε + on)) : mul_le_mul_of_nonneg_left !min_le_right (le_of_lt Hε)
... < ε / 2 : mul_div_self_add_lt (div_pos_of_pos_of_pos Hε two_pos) Hε !op_norm_pos,
exact calc
on * ∥x' - x∥ < on * min δ ((ε / 2) / (ε + on)) : mul_lt_mul_of_pos_left Hx' !op_norm_pos
... ≤ on * ((ε / 2) / (ε + on)) : mul_le_mul_of_nonneg_left !min_le_right (le_of_lt !op_norm_pos)
... < ε / 2 : mul_div_add_self_lt (div_pos_of_pos_of_pos Hε two_pos) Hε !op_norm_pos}
end
theorem continuous_at_of_has_frechet_deriv_at {A : V → W} [is_bdd_linear_map A]
(H : has_frechet_deriv_at f A x) : continuous_at f x :=
begin
apply @continuous_at_of_diffable_at,
existsi A,
exact H
end
end frechet_deriv
section comp
lemma div_mul_div_cancel {A : Type} [field A] (a b : A) {c : A} (Hc : c ≠ 0) : (a / c) * (c / b) = a / b :=
by rewrite [-mul_div_assoc, div_mul_cancel _ Hc]
lemma div_add_eq_add_mul_div {A : Type} [field A] (a b c : A) (Hb : b ≠ 0) : (a / b) + c = (a + c * b) / b :=
by rewrite [-div_add_div_same, mul_div_cancel _ Hb]
-- I'm not sure why smul_approaches doesn't unify where I use this?
private lemma real_limit_helper {U : Type} [normed_vector_space U] {f : U → } {a : } {x : U}
(Hf : f ⟶ a [at x]) (c : ) : (λ y, c * f y) ⟶ c * a [at x] :=
begin
apply smul_approaches,
exact Hf
end
variables {U V W : Type}
variables [HU : normed_vector_space U] [HV : normed_vector_space V] [HW : normed_vector_space W]
variables {f : V → W} {g : U → V}
variables {A : V → W} {B : U → V}
variables [HA : is_bdd_linear_map A] [HB : is_bdd_linear_map B]
variable {x : U}
include HU HV HW HA HB
-- this takes 2 seconds without clearing the contexts before simp
theorem has_frechet_deriv_at_comp (Hg : has_frechet_deriv_at g B x) (Hf : has_frechet_deriv_at f A (g x)) :
@has_frechet_deriv_at _ _ _ _ (λ y, f (g y)) (λ y, A (B y)) !is_bdd_linear_map_comp x :=
begin
unfold has_frechet_deriv_at,
note Hf' := has_frechet_deriv_at_elim Hf,
note Hg' := has_frechet_deriv_at_elim Hg,
have H : ∀ h, f (g (x + h)) - f (g x) - A (B h) =
(A (g (x + h) - g x - B h)) + (-f (g x) + f (g (x + h)) + A (g x - g (x + h))),
begin intro; rewrite [3 hom_sub A], clear [Hf, Hg, Hf', Hg'], simp end, -- .5 seconds for simp
have H' : (λ h, ∥f (g (x + h)) - f (g x) - A (B h)∥ / ∥h∥) =
(λ h, ∥(A (g (x + h) - g x - B h)) + (-f (g x) + f (g (x + h)) + A (g x - g (x + h)))∥ / ∥h∥),
from funext (λ h, by rewrite H),
rewrite H',
clear [H, H'],
apply approaches_squeeze, -- show the limit holds by bounding it by something that vanishes
{apply approaches_constant},
rotate 1,
{apply filter.eventually_of_forall, intro, apply div_nonneg_of_nonneg_of_nonneg, repeat apply norm_nonneg},
{apply filter.eventually_of_forall, intro,
apply div_le_div_of_le_of_nonneg,
apply norm_triangle,
apply norm_nonneg},
have H : (λ (y : U), (∥A (g (x + y) - g x - B y)∥ + ∥-f (g x) + f (g (x + y)) + A (g x - g (x + y))∥) / ∥y∥) =
(λ (y : U), (∥A (g (x + y) - g x - B y)∥ / ∥y∥ + ∥-f (g x) + f (g (x + y)) + A (g x - g (x + y))∥ / ∥y∥)),
from funext (λ y, by rewrite [div_add_div_same]),
rewrite [H, -zero_add 0], -- the function is a sum of two things that both vanish
clear H,
apply add_approaches,
{apply approaches_squeeze, -- show the lhs vanishes by squeezing it again
{apply approaches_constant},
rotate 1,
{apply filter.eventually_of_forall, intro, apply div_nonneg_of_nonneg_of_nonneg, repeat apply norm_nonneg},
{apply filter.eventually_of_forall, intro y,
show ∥A (g (x + y) - g x - B y)∥ / ∥y∥ ≤ op_norm A * (∥(g (x + y) - g x - B y)∥ / ∥y∥), begin
rewrite -mul_div_assoc,
apply div_le_div_of_le_of_nonneg,
apply op_norm_bound A,
apply norm_nonneg
end},
{rewrite [-mul_zero (op_norm A)],
apply real_limit_helper,
apply Hg}}, -- we have shown the lhs vanishes. now the rhs
{have H : ∀ y, (∥-f (g x) + f (g (x + y)) + A (g x - g (x + y))∥ / ∥y∥) =
((∥(f (g (x + y)) - f (g x)) - A (g (x + y) - g x) ∥ / ∥g (x + y) - g x∥) * (∥g (x + y) - g x∥ / ∥y∥)),
begin
intro,
cases em (g (x + y) - g x = 0) with Heq Hneq,
{note Heq' := eq_of_sub_eq_zero Heq,
rewrite [Heq', neg_add_eq_sub, *sub_self, hom_zero A, add_zero, *norm_zero, div_zero, zero_div]},
{rewrite [div_mul_div_cancel _ _ (norm_ne_zero_of_ne_zero Hneq), *sub_eq_add_neg,
-hom_neg A],
clear [Hf, Hg, Hf', Hg', Hneq],
simp} --(.5 seconds)
end,
apply approaches_squeeze, -- again, by squeezing
{apply approaches_constant},
rotate 1,
{apply filter.eventually_of_forall, intro, apply div_nonneg_of_nonneg_of_nonneg, repeat apply norm_nonneg},
{apply filter.eventually_of_forall, intro y, rewrite H,
apply mul_le_mul_of_nonneg_left,
{show ∥g (x + y) - g x∥ / ∥y∥ ≤ ∥g (x + y) - g x - B y∥ / ∥y∥ + op_norm B, begin
cases em (y = 0) with Heq Hneq,
{rewrite [Heq, norm_zero, *div_zero, zero_add], apply le_of_lt, apply op_norm_pos},
rewrite [div_add_eq_add_mul_div _ _ _ (norm_ne_zero_of_ne_zero Hneq)],
apply div_le_div_of_le_of_nonneg,
apply le.trans,
rotate 1,
apply add_le_add_left,
apply op_norm_bound,
apply norm_nonneg,
rewrite [-neg_add_cancel_right (g (x + y) - g x) (B y) at {1}, -sub_eq_add_neg],
apply norm_triangle
end},
{apply div_nonneg_of_nonneg_of_nonneg, repeat apply norm_nonneg}},
-- now to show the bounding function vanishes. it is a product of a vanishing function and a convergent one
apply mul_approaches_zero_of_approaches_zero_of_approaches,
{have H' : (λ (y : U), ∥f (g (x + y)) - f (g x) - A (g (x + y) - g x)∥ / ∥g (x + y) - g x∥) =
(λ (y : U), ∥f (g x + (g (x + y) - g x)) - f (g x) - A (g (x + y) - g x)∥ / ∥g (x + y) - g x∥),
from funext (λ y, by rewrite [add.comm (g x), sub_add_cancel]), -- first, show lhs vanishes
rewrite H',
have Hgcts : continuous_at (λ y, g (x + y) - g x) 0, begin
apply normed_vector_space.continuous_at_intro,
intro ε Hε,
cases normed_vector_space.continuous_at_dest (continuous_at_of_has_frechet_deriv_at g x Hg) _ Hε with δ Hδ,
existsi δ,
split,
exact and.left Hδ,
intro x' Hx',
rewrite [add_zero, sub_self],
rewrite sub_zero,
apply and.right Hδ,
have (x + x') - x = x' - 0, begin clear [Hg, Hf, Hf', Hg', H, H', Hδ, Hx'], simp end, -- (.6 seconds w/o clear, .1 with)
rewrite this,
apply Hx'
end,
have Hfcts : continuous_at (λ (x' : V), ∥f (g x + x') - f (g x) - A x'∥ / ∥x'∥) (g (x + 0) - g x), begin
rewrite [add_zero, sub_self],
apply diff_quot_cts,
exact Hf
end,
have Heqz : ∥f (g x + (g (x + 0) - g x)) - f (g x) - A (g (x + 0) - g x)∥ / ∥g (x + 0) - g x∥ = 0,
by rewrite [*add_zero, sub_self, norm_zero, div_zero],
apply @tendsto_comp _ _ _ (λ y, g (x + y) - g x),
apply tendsto_inf_left,
apply tendsto_at_of_continuous_at Hgcts,
note Hfcts' := tendsto_at_of_continuous_at Hfcts,
rewrite Heqz at Hfcts',
exact Hfcts'}, -- finally, show rhs converges to op_norm B
{apply add_approaches,
apply Hg,
apply approaches_constant}}
end
end comp
end analysis